The COVID-19 pandemic and refugees. A scoping review - Deliu Alexandra; Voicu Bogdan; Glăvan Eugen (Social Change Review, 2023)
Refugees increasingly become part of the European societies. Afghans, Syrians, Ukrainians fled their countries due to war, conflicts, persecution, and settled, temporary or not, in more stable countries. During pandemics, with openness towards foreigners shrinking, and borders closing, the situation of refugees might become uncertain. Our scoping review explores what academics considered relevant about refugees to Europe in relation to the COVID-19 pandemic. The findings reveal increasing resentment against immigrants, a need for redesigning European migration policies, preparing welfare systems, asylum protection mechanisms, and societies as a whole, in order to prevent disruptions in the eventuality of large-scale crises. Such implications are to also be considered for the consequences of the current Russian aggression on Ukraine.